ECONOMIC, ENVIRONMENTAL AND SOCIAL FACTORS AS CORPORATE SOCIAL RESPONSIBILITY DIMENSIONS ON THE FINANCIAL PERFORMANCE OF THE PHARMACEUTICAL SECTOR ON THE INDONESIA STOCK EXCHANGE - Yuniep Mujati Sudaidah (SEAN Institute, 2023)
The purpose of this study was to determine the effect of CSR with economic, environmental and social dimensions on the financial performance of the pharmaceutical sector on the Indonesian Stock Exchange. This type of research is quantitative descriptive. The study population was 12 pharmaceutical sector companies, the sampling technique was purposive sampling, the sample used was 108 data. The data used is secondary data by collecting data through documentation. Data analysis using multiple linear regression. The results of the discussion show that there is a positive but not significant effect of CSR disclosure on the economic dimension of the financial performance of the pharmaceutical sector in Indonesia. There is a significant positive effect of CSR disclosure on the environmental dimension on the financial performance of the pharmaceutical sector in Indonesia. There is a positive and insignificant effect of social dimension CSR disclosure on the financial performance of the pharmaceutical sector in Indonesia.